TEST OF SPEED OF ADJUSTMENT TOWARDS THE CAPITAL STRUCTURE IN INDONESIA TELECOMMUNICATION INDUSTRY - Riko Hendrawan; Dwipanca Adi Nugraha (Jurnal Keuangan dan Perbankan, 2015)
The purpose of this research was to test whether or not the pecking order theory occurred in telecommunication industry in Indonesia and also in its speed of adjustment.  Using the purposive sampling method and taking 7 years period of data collection from 2006 up to 2012, the data were gathered from the companies’ financial statement. The data were analyzed using the random effect model of Hausman test with interest bearing debt as its dependent variable and deficit as its independent variable.  Finding from this research showed that  pecking order theory was not applied in the telecommunication industry in Indonesia and it was quite different from the finding of Huang Ritter (2009) that publicly traded firms in US adjusted to their target leverage at a moderate speed with a period of 3.9 years. It also discovered that the fastest growth of the speed of adjustment was shown by XL Axiata with -493.96% per year, and then Bakrie Telecom with -65.62%. Indosat and Telkom Indonesia showed a different behavior with a slower speed of adjustment Indosat with 13.22%, and Telkom Indonesia with 274.14% slower.